Non-invasive imaging of single human motor units - Birkbeck, Matthew G. (Clin Neurophysiol, 2020)
OBJECTIVE: To determine the size, shape and distribution of single human motor units in-vivo in healthy controls of different ages. METHODS: A novel diffusion-weighted magnetic resonance imaging (MRI) technique was used in combination with in-scanner electrical stimulation to quantify the shape, cross-sectional area, and dimensions of individual motor units in 10 healthy subjects. RESULTS: Thirty-one discrete motor units were studied. The majority were elliptical or crescent shaped, but occasional split motor units were observed. The mean motor unit cross sectional area was 26.7 ± 11.2 mm(2), the mean maximum dimension was 10.7 ± 3.3 mm, and the mean minimum dimension was 4.5 ± 1.2 mm. Subjects aged over 40 had significantly larger maximum dimensions than those below this age (p < 0.05). CONCLUSIONS: Motor unit MRI (MUMRI) is a novel technique capable of revealing the size, shape and position of multiple motor units in human muscles. It is reproducible, non-invasive, and sufficiently sensitive to detect physiologically relevant changes in motor unit morphology with age. SIGNIFICANCE: To our knowledge, these results provide the first imaging assessment of human motor unit morphology. The technique shows promise both as a diagnostic tool and as a biomarker in longitudinal studies of disease progression.